The Effect of Use Mobile Payment on Purchasing Decision Case Study: Link Aja - Putu Nurwita Pratami Wijaya, Ni; Astuti P, Sri; Hardiyanto, Nugroho (International Journal of Psychosocial Rehabilitation, 2020)
The increasing interest in public spending has caused many companies to issue various types of forms of payment in mobile payment. One reason for the company to release products via mobile payment is to provide services to its customers in terms of the ease of transactions. So the purpose of this study is to see the effect of the ease of transactions by using mobile payment on purchasing decisions. The research method used in this study is regression analysis. The data obtained comes from primary data, which conducts field research in the form of interviews and questionnaires, and secondary data, namely by studying literature, archives, and documents. The sample was distributed to 100% of respondents as mobile payment link users.